Revisitasi Islam Politik dan Islam Kultural di Indonesia - Azyumardi Azra (JURNAL INDO-ISLAMIKA, 2012)
This article discusses two faces of Islam, political and cultural, which have developed throughout the Muslim world, including in Indonesia. It argues that political Islam has two faces and both of which, although represented by two different groups, have the same agendas, i.e., the application by the state of shari’a, and also the establishment of Islamic state. Arguing that political Islam has brought about radicalism, the article proposes that the other face of Islam, that is cultural Islam, should be maintained and empowered.